2016
DOI: 10.1039/c6tc00655h
|View full text |Cite
|
Sign up to set email alerts
|

Impact of aggregation on fluorescence sensitivity of molecular probes towards nitroaromatic compounds

Abstract: Aggregation of the molecular probe increases its fluorescence sensitivity towards nitroaromatic explosives by the order of 103to 105.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Imidazolium based fluorescent probes 113-115 111 (chart 13) were used for detection of nitroaromatic like as PA, 2,4-DNP, TNT and ClDNB in water-DMSO (98: 2). Among three probes, probe 113 did not undergo aggregation and remained in the molecularly dissolved state due to short alkyl chains but another two probes 114 and 115 self-assembled in water.…”
Section: Tripodal Tricationic Fluorescent Probes For Picric Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…Imidazolium based fluorescent probes 113-115 111 (chart 13) were used for detection of nitroaromatic like as PA, 2,4-DNP, TNT and ClDNB in water-DMSO (98: 2). Among three probes, probe 113 did not undergo aggregation and remained in the molecularly dissolved state due to short alkyl chains but another two probes 114 and 115 self-assembled in water.…”
Section: Tripodal Tricationic Fluorescent Probes For Picric Acidmentioning
confidence: 99%
“…Further, the detection of vapor of picric acid by fluorescent probe can give advantage for the device formation. However, only in a couple of cases, thin films 108,109,111,120 of probe undergo fluorescence quenching with picric acid within couple of minutes and in other cases the probe deposited on TLC plate 53,89 or the solution of probe in THF-water 33 detect picric acid vapor.…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 99%
“…[20,21] Recently,w eh ave shown that the positivelyc harged architect of the N-aryl benzimidazolium (BIm) group combines electrostatic and hydrogen-bonding properties;t hus providing beneficial effectso fi ncreased water solubility,i ncreased CÀHp olarization,a nd the possibility of sensing anionst hrough (ionic) self-assembly. [22][23][24] Ionic self-assembly of two structurally different and charged building blocks to create nanostructured supramolecular materials is aw ell-knownp henomenoni nc olloidal science. [25][26][27][28] Indeed, making aj udicious choice of buildingb locks to match the size, complementarity,a nd electrostatic interactions between two oppositely chargedc omponentsp lays av ital role in the initiation of ionic self-assembly.…”
Section: Introductionmentioning
confidence: 99%
“…Such disintegration of nanorods to spheres has earlier been observed during encapsulation of picrate anions by nanorods of the tripodal system. 34,35…”
mentioning
confidence: 99%
“…Such disintegration of nanorods to spheres has earlier been observed during encapsulation of picrate anions by nanorods of the tripodal system. 34,35 Interestingly, upon the addition of other analytes such as Br À , CN À , Cys, ClO 4 À , OH À , F À , HCy, SO S8, ESI †). Moreover, the addition of triethylamine and glutathione to the solution of PDI 1 does not induce any formation of PDI 1 À (Fig.…”
mentioning
confidence: 99%